Effect of molybdenum stress on growth, yield and seed quality in black gram. (20th March 2016) - Gopal, Rajeev; Sharma, Yogesh K.; Shukla, Arvind K.
ABSTRACT: Black gram ( Vigna mungo L.) var. Shyam plants were raised in refined sand at four levels of molybdenum (Mo), i.e., low (0.002 µM) to excess (2 µM) for 70 days. The molybdenum deficiency symptoms appeared as interveinal chlorosis of young and middle leaves. Compared to control (0.2 µM Mo), total dry matter, seed yield and seed protein decreased at low and excess Mo. The concentration of Mo in leaves and seed as well as activity of nitrate reductase increased with an increase in Mo supply. Low and excess Mo deteriorated the quality of seeds by lowering the content of starch, sugars, protein, and nitrogen and increasing electrical conductivity of seed leachate. Molybdenum deficiency and excess both resulted in production of lightweight immature seeds, poor in vigor and germination potential. The values of sufficiency and threshold of toxicity in leaves were 0.078 and 2.15 µg Mo g −1 dry matter of black gram.